Dynamically Tunable Deep Subwavelength High‐Order Anomalous Reflection Using Graphene Metasurfaces. Issue 3 (27th December 2017) - Wang, Chao; Liu, Wenwei; Li, Zhancheng; Cheng, Hua; Li, Zhi; Chen, Shuqi; Tian, Jianguo
Abstract: Graphene‐based metasurfaces have emerged as promising photoelectric devices that can dynamically control the behavior of electromagnetic waves. The high‐order anomalous reflection provides an additional degree of freedom in the field of photonic research. Here, a series of gradient graphene metasurfaces with high‐order modes to manipulate the wavefront of reflected light is proposed. By properly arranging the graphene nanostructures, 5‐order anomalous reflection and 15‐order high‐quality Laguerre–Gaussian beams are achieved. Furthermore, the efficiency of the metasurfaces is dynamically controlled by tuning the electrostatic gating to change the Fermi energy of graphene. This work offers a new idea for the development of tunable wavefront‐controlling devices and contributes to a wide range of applications in photonic systems. Abstract : A series of gradient graphene metasurfaces with high‐order modes can achieve deep subwavelength modulation in the infrared waveband. The 5‐order anomalous reflection and 15‐order high‐quality Laguerre–Gaussian beams are achieved. Furthermore, the efficiency of the metasurfaces can be dynamically controlled by tuning the electrostatic gating to change the Fermi energy of graphene.